Glucose modulates the binding of an islet-specific factor to a conserved sequence within the rat I and the human insulin promoters. - Melloul, D (1993)
In cultured rat and human pancreatic islets, glucose stimulated transcription of the rat insulin I gene through the mini-enhancer (FF) located between residues -196 and -247. The glucose-sensitive element was delineated to the region -193 to -227. The mini-enhancer bound islet nuclear proteins to form three major complexes (C1-C3). A 22-bp subfragment, spanning the sequence -206 to -227, was sufficient to retain all binding activities of the entire FF. The homologous sequence of the human insulin promoter interacted with rat islet nuclear extracts to form a single complex, corresponding to the C1 complex of the rat insulin I sequence. C1 was present only in insulin-producing cells; it was the major complex detected in isolated human islets with both rat and human insulin sequences. Furthermore, the DNA binding activity of the C1 factor(s) was selectively modulated by extracellular glucose in a dose-dependent manner; a 4.5-fold increase in binding intensity was detected when rat islets were incubated for 1-3 h in the presence of 20 vs. 1-2 mM glucose. We therefore suggest that the factor(s) involved in the C1 complex corresponds to the glucose-sensitive factor and, consequently, may play a determining role in glucose-regulated expression of the insulin gene.